OS IMPACTOS SOCIOECONÔMICOS DOS INCÊNDIOS FLORESTAIS NAS COMUNIDADES PANTANEIRAS DA SUB-REGIÃO DO PARAGUAI - Tayrine Pinho de Lima Fonseca (2024)
In the Pantanal, forest fires have made national and international headlines in 2020 and 2021, usually focusing on the environmental damage and the vast territorial extent affected. However, there has been little discussion of the recurring and persistent impacts that these fires have on both the ecosystem and society, especially in the communities that live on the banks of the Paraguay River and its tributaries in the Pantanal plain, especially Barra do São Lourenço Community, Aterro do Binega, Porto do Amolar and Paraguai-Mirim Community. From this context, the general objective is analyzing fire scars and socio-economic impacts in the Pantanal. The specific objectives are: spatially analyze the fire scars of the years 2020 and 2021 in the Paraguay sub-region; to identify the socio-economic impacts of forest fires along the Paraguay River in the Corumbá-Serra do Amolar stretch in the perception of Pantanal residents; and to describe the use and management of fire in Pantanal communities in the Paraguay sub-region. To carry out the research, a mixed method was used, combining qualitative and quantitative approaches. The first was based on secondary data from MapBiomas and INPE Queimadas, as well as the use of geotechnologies to spatialize fire scars. Using Qgis – Geographic Information System (GIS), satellite images were geoprocessed in a multi-temporal analysis, covering the months of July to December, which represent the most critical periods for forest fires in the Pantanal biome. The second included field research with two different groups: Pantanal community and the tourism sector. Interviews, photographic records and an analysis by triangulation of methods were carried out. The main results revealed that, in 2020, the fire spots were concentrated in the north of the Paraguay sub-region, near the Serra do Amolar. In 2021, the fires clustered near the border between Brazil and Bolivia and in the Corumbá port area, following the Paraguay River. In qualitative terms, the indirect impacts of the forest fires on the Pantanal communities were widely perceived by the affected residents, who reported loss of materials, changes in daily life, lack of drinking water and difficulties in carrying out artisanal fishing, both for fish and live bait. Economically, the population’s source of income was already weakened by the effects of the pandemic, and the forest fires increased vulnerability. In addition, we analyzed the use and management of fire by local populations, who maintain ancestral practices, and the changes in habits after the 2020 forest fire, driven by the instructions on preparation, prevention and firefighting provided by environmental agencies and NGOs. These changes culminated in the formation of community brigades, created with the aim of protecting human lives, the areas around homes and small outbreaks of fire in the Pantanal. The main contribution of this research is that the socio-economic impacts of forest fires in the Pantanal go beyond the physical scars left by the fire. It shows that the lives of residents during these events are impacted not only in terms of physical and mental health, but also in terms of sources of income. Therefore, future public policies for the preservation and conservation of the Pantanal should consider both the ecosystem and the permanence and quality of life of local populations. Keywords: forest fire; Pantanal; fires; Pantanal communities.